The Relationship of Sleep Hygiene with Anxiety in Patients with Diabetes Mellitus in the Working Area of the Dungingi Health Center - Natasya Pratiwi Abidin; Andi Nuraina Sudirman; Nur Uyuun I. Biahimo; Sabirin B. Syukur (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Sleep hygiene is a habit that supports healthy sleep, such as maintaining a sleep routine and creating a comfortable sleeping environment. Sleep hygiene plays a role in sleep quality and psychological conditions, including anxiety, especially in patients with diabetes mellitus (DM). DM patients often experience sleep disorders that can increase anxiety., This study aims to determine the relationship between sleep hygiene and anxiety in DM patients at the Dungingi Health Center. The study used a quantitative method of cross-sectional design, with a population of 56 and involving 35 patients selected by purposive sampling. Sleep hygiene is measured by the Sleep Hygiene Index (SHI) and anxiety levels by the State-Trait Anxiety Inventory (STAI). The results showed that 57.1% of respondents had poor sleep hygiene, and 62.9% were in the category of moderate to high anxiety. There was a significant association between sleep hygiene and anxiety (p = 0.000), which suggests that sleep hygiene is not good in relation to increased anxiety in DM patients. and The conclusion of this study is that there is a significant relationship between poor sleep hygiene and increased anxiety levels in patients with diabetes mellitus